صيانة السلم والأمن الدوليين ضمن إطار الأمم المتحدة في ظلّ سيطرة القوى الكبرى - خضور, بسام محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى بيان أهمية مجلس الأمن التابع لمنظمة الامم المتحدة، ودوره في الحفاظ على السلم والأمن الدوليين. كما يلقي الضوء على أهم الانتقادات الموجهة لمجلس الأمن بما في ذلك بيان ضرورة إعادة إصلاحه من أجل إعادة الفعالية لهذه المنظمة وتحسين وظائفها وعملها، وتحقيق نوع من الديموقراطية العالمية، والعمل على تحقيق مبدأ العدل والمساواة بين الدول من أجل الحفاظ على السلم والأمن الدوليين والقدرة على الخروج بقرارات تخدم الصالح العام للدول دون أن تبنى هذه القرارات على أساس المصالح الشخصية للأعضاء الدائمين في مجلس الأمن. This research aims to demonstrate the importance of the United Nations Security Council and its role in the maintenance of international peace and security. It also sheds light on the most important criticisms against the Security Council, including the need to reform it in order to restore the effectiveness of this Organization, improve its functions and work, achieve a kind of global democracy, work towards the realization of the principle of justice and equality among States in order to maintain international peace and security and to make decisions that serve the common interest of States without the adoption of such resolutions on the basis of the personal interests of the permanent members of the Security Council.